Determinan Indeks Pembangunan Manusia Di Kabupaten Lampung Tengah, Provinsi Lampung, Indonesia - Dedy Hermawan (Sawala : Jurnal Administrasi Negara, 2019)
United Nations has been changed Millennium Development Goals (MDGs) into Sustainable Development Goals (SDGs). This change has been strengthening human development as one of SDGs pillar beside economic development, ecology development, and institutional development. One of the global instruments to explain human development is the Human Development Index (HDI). Today, one of academic debate surrounding the HDI is what is the determinant of HDI. Based on secondary data in Central Lampung District, Lampung Province, Indonesia, this paper attempt to examine the relationship between independent variables (RLS, HLS, AHH, and PKP) and IPM as the dependent variable. The result shows that RLS, HLS, AHH, and PKP have a positive relationship with IPM. However, each variable has a different effect on IPM. We find that RLS and HLS is the most significant contributor for the IPM. We discuss the theoretical and practical implication this finding in the context of Lampung Province and Central Lampung District.